Parliament and the Press: Forging the United Nations in Wartime Britain, 1939–45. (2nd June 2020) - Holmila, Antero
Abstract: During the Second World War,  not only the United States but also Great Britain played a leading role in planning and establishing the United Nations (UN) as a new international organisation to replace the League of Nations. While scholarship on post‐war planning is extensive, relatively little exists on how the planning process was discussed and depicted publicly in Britain. The purpose of this article is to fill such lacunae by examining the two most important domains for public discussion at the time, the press and parliament. It will argue, first, that the League of Nations' experience – its inability to use collective force and its optimistically democratic structure – overwhelmingly shaped public discourse in reference to the UN. By referring to the past, the press and politicians alike in Britain were content to relinquish interwar ideas such as equal rights and equal representation for all nations. Second, apart from the lessons of history, the less democratic structure of the new world organisation was justified from the perspective of great power politics. The desire to make the grand alliance between Britain, the United States of America, and the USSR functional despite all mutual suspicions, directed the view of the UN, and typically overrode all other concerns relating to post‐war planning. Finally, throughout the wartime planning of the UN, public opinion, in so far as press and parliament were concerned, held fast to the idea that the British empire was not to be touched by the UN. In public, the establishment of the UN was hardly considered as a starting point for decolonisation. Instead, the UN was designed to become the post‐war embodiment of the grand alliance, a vehicle through which the victory over the Axis powers would be managed at the global level: such management did not envision the need to let empire go. Viewed this way, it also becomes clear that nationalism and internationalism were not mutually exclusive or binary visions, but coexisted and shifted in importance throughout the period examined.